Diagnostic accuracy of the Leishmania OligoC-TesT and NASBA-Oligochromatography for diagnosis of leishmaniasis in Sudan. - Alfarazdeg A Saad; Nuha G Ahmed; Osman S Osman; Ahmed Almustafa Al-Basheer; Awad Hamad; Stijn Deborggraeve; Philippe Büscher; Gerard J Schoone; Henk D Schallig; Thierry Laurent; Ahmed Haleem; Omran F Osman; et al. (Public Library of Science (PLoS), 2010)
Background The Leishmania OligoC-TesT and NASBA-Oligochromatography (OC) were recently developed for simplified and standardised molecular detection of Leishmania parasites in clinical specimens. We here present the phase II evaluation of both tests for diagnosis of visceral leishmaniasis (VL), cutaneous leishmaniasis (CL) and post kala-azar dermal leishmaniasis (PKDL) in Sudan. Methodology The diagnostic accuracy of the tests was evaluated on 90 confirmed and 90 suspected VL cases, 7 confirmed and 8 suspected CL cases, 2 confirmed PKDL cases and 50 healthy endemic controls from Gedarif state and Khartoum state in Sudan. Principal findings The OligoC-TesT as well as the NASBA-OC showed a sensitivity of 96.8% (95% CI: 83.8%-99.4%) on lymph node aspirates and of 96.2% (95% CI: 89.4%-98.7%) on blood from the confirmed VL cases. The sensitivity on bone marrow was 96.9% (95% CI: 89.3%-99.1%) and 95.3% (95% CI: 87.1%-98.4%) for the OligoC-TesT and NASBA-OC, respectively. All confirmed CL and PKDL cases were positive with both tests. On the suspected VL cases, we observed a positive OligoC-TesT and NASBA-OC result in 37.1% (95% CI: 23.2%-53.7%) and 34.3% (95% CI: 20.8%-50.9%) on lymph, in 72.7% (95% CI: 55.8%-84.9%) and 63.6% (95% CI: 46.6%-77.8%) on bone marrow and in 76.9% (95% CI: 49.7%-91.8%) and 69.2% (95% CI: 42.4%-87.3%) on blood. Seven out of 8 CL suspected cases were positive with both tests. The specificity on the healthy endemic controls was 90% (95% CI: 78.6%-95.7%) for the OligoC-TesT and 100% (95% CI: 92.9%-100.0%) for the NASBA-OC test. Conclusions Both tests showed high sensitivity on lymph, blood and tissue scrapings for diagnosis of VL, CL and PKDL in Sudan, but the specificity for clinical VL was significantly higher with NASBA-OC.